2016
DOI: 10.1152/japplphysiol.00837.2015
|View full text |Cite
|
Sign up to set email alerts
|

A putative low-carbohydrate ketogenic diet elicits mild nutritional ketosis but does not impair the acute or chronic hypertrophic responses to resistance exercise in rodents

Abstract: We examined whether acute and/or chronic skeletal muscle anabolism is impaired with a low-carbohydrate diet formulated to elicit ketosis (LCKD) vs. a mixed macronutrient Western diet (WD). Male Sprague-Dawley rats (9-10 wk of age, 300-325 g) were provided isoenergetic amounts of a LCKD or a WD for 6 wk. In AIM 1, basal serum and gastrocnemius assessments were performed. In AIM 2, rats were resistance exercised for one bout and were euthanized 90-270 min following exercise for gastrocnemius analyses. In AIM 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
(40 reference statements)
2
33
0
Order By: Relevance
“…This observation could be a result of increased AMPK activation, an important signaling event in mitochondrial biogenesis and function (Kennedy et al, 2007), induced by KD. However, previous report on these animals observed no differences in p-AMPK (Roberts et al, 2016). This observation was attributed to adaptation to the ketogenic diet and a resetting of AMPK signaling, thus the differences in significance from our current findings may be due to adaptations earlier in training while adaptation to the KD was taking place (Roberts et al, 2016).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This observation could be a result of increased AMPK activation, an important signaling event in mitochondrial biogenesis and function (Kennedy et al, 2007), induced by KD. However, previous report on these animals observed no differences in p-AMPK (Roberts et al, 2016). This observation was attributed to adaptation to the ketogenic diet and a resetting of AMPK signaling, thus the differences in significance from our current findings may be due to adaptations earlier in training while adaptation to the KD was taking place (Roberts et al, 2016).…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, animals exposed to resistance wheel exercise training had increases in mitochondrial complex activity, mRNA expression of genes involved in metabolism, and endogenous antioxidant protein expression. Previous observation on the hypertrophic response of these animals by Roberts et al demonstrated increased markers of ketogenesis indicating that KD-fed animals expressed “mild” ketosis (Roberts et al, 2016). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In skeletal muscle, the KD increased p-4E-BP1 levels. Similarly, a recent study in rats fed a relatively high protein (~20% kcal) ketogenic diet detected no change in p-rpS6 and a trend towards an increase in p-4E-BP1 (Roberts et al, 2016). Thus, protein level may have a major influence on mTORC1 signal in response to a KD.…”
Section: Discussionmentioning
confidence: 79%
“…These changes are at least partially due to reduced anti-lipolytic insulin action and protein-protective action of increased total and free thyroxine index after a LCHF diet (Volek et al, 2002). Furthermore, a LCHF diet led to a similar magnitude increase in the muscle protein synthesis rate, activation of AMP-activated protein kinase and 4E-binding protein-1 compared to a HCLF diet after resistance exercise in rats (Roberts et al, 2016). Therefore, it is possible that LCHF diets, in combination with resistance training, can maintain fat-free mass while receiving the benefit of loss in fat mass and body weight.…”
Section: Lchf Diet and Body Compositionmentioning
confidence: 99%